PERAN MANAJEMEN LEMBAGA PENDIDIKAN ISLAM DALAM MENGHADAPI TANTANGAN GLOBAL DI MTs BINA TARUNA MARELAN - Anggraini, Nadia; Saraini, Ihsan; Maghfiroh, Lusi; Febriyan, Rio (Yayasan Pendidikan Islam Akmalia, 2022)
Globalization brings a very significant change impact, especially on changes in the behavior of each individual. The link between globalization and education lies in the birth of a new society characterized by a